Determination of Complete Blood Count Reference Values of Mindray BC-760 Hematology Analyzer - Iriani, Anggraini; Armenia, Dhinasty; Putri, Dian Eka; Shafwandi, Ritki Fazapadena; Murdianto, Rendy; Aditya, Legina; Purnamasari, Endah; Bahri, Syukrini; Aprilio, Henri; Poerwantoro, Bambang (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Hematological assessment serves as a standard examination in supporting diagnostics in clinical practice. The advanced hematology analyzer instrument namely Mindray BC 760 has recently introduced several new hematological parameters which previously unavailable. This study set out to establish the value of the reference interval of those new parameters on the Mindray BC 760 device in the Indonesian adult population. This observational study took place at Yarsi Hospital, Jakarta from March to August 2023. A total of 352 subjects who underwent medical check-ups at pathology clinics laboratory in the hospital were enrolled. All participants comprised both females and males aged > 17 years and were confirmed to be healthy through examination. Hematological assessment using Mindray BC 760 device. A remarkable significant difference was observed between females and males (p< 0.05) in terms of Hb, RBC, MCH, MCHC, RHE, RET, PLT, PDW, PCT, PLCC, Monocyte and eosinophil count, and neutrophil%. Conversely, MCV, RDW-SD, RET%, IRF, LFR, MFR, HFR, NRBC, NRBC%, WBC, NEU, LYM, BAS, IMG, LYM%, BAS%, IMG%, MPV, IPF showed no significant differences based on gender. It is recommended to adjust of reference interval value according to gender for several novel hematological parameters assessed through the Mindray BC 760 instrument.